A Tripartite Evolutionary Game Analysis on The Co-construction of Fresh Food Supply Chain System with Blockchain Technology - Zhang, Rong; Zhai, Zhenjie (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
Eliminating Information asymmetry and food safety risks in the fresh food supply chain with the help of blockchain technology has become one of the hot topics in academic and agricultural fields. However, as the non-rational stakeholders in the fresh food supply chain, ensuring that the three parties can actively participate in the construction of the blockchain system is a complex problem. This paper constructs a tripartite evolutionary game model among the cooperative(farmers), fresh food retailers, and third-party logistics providers, and then obtains the replicator dynamics function of stakeholders and analyzes the evolution trend in the co-construction of the fresh food supply chain system with blockchain technology. The results show that three Evolutionary Stable Strategies (ESS) are accepted by three players under specific parameters, and the equilibrium point remains stable under external interference. Moreover, the existence of an ideal cooperative state where all three players choose to participate actively has been confirmed. When blockchain systems generate additional benefits, they can incentivize active participation from stakeholders, and consumer attitudes toward traceable agricultural products actively correlate with these benefits. The blockchain protocol restricts participants, but excessively harsh penalties may inhibit sales and the involvement of third-party logistics (3PL).